2022
DOI: 10.1002/lary.30101
|View full text |Cite
|
Sign up to set email alerts
|

Modified Olfactory Training Is an Effective Treatment Method for COVID‐19 Induced Parosmia

Abstract: Objectives Coronavirus disease (COVID‐19) infection often causes olfactory dysfunction and parosmia may occur in some patients with olfactory dysfunction. In this study, we retrospectively investigated the effectiveness of modified olfactory training (MOT) for the treatment of COVID‐19‐induced parosmia. Study Design This study presents results of MOT performed with 12 odors for 36 weeks in patients with olfactory dysfunction following COVID‐19 infection. A total of 75 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 21 publications
1
38
0
1
Order By: Relevance
“…It also supports the use of SCENTinel 1.1 as a tool to help detect and monitor sudden loss of smell, which is a symptom of COVID-19 (5,55), as well as parosmia, an evolving symptom of COVID-19 (31,36,37). Early diagnosis of olfactory impairment is critical for establishing successful outcomes to treatment regimes like olfactory training (56) which has recently shown effectiveness with patients with parosmia (57).…”
Section: Discussionmentioning
confidence: 99%
“…It also supports the use of SCENTinel 1.1 as a tool to help detect and monitor sudden loss of smell, which is a symptom of COVID-19 (5,55), as well as parosmia, an evolving symptom of COVID-19 (31,36,37). Early diagnosis of olfactory impairment is critical for establishing successful outcomes to treatment regimes like olfactory training (56) which has recently shown effectiveness with patients with parosmia (57).…”
Section: Discussionmentioning
confidence: 99%
“…51 OT is maximally efficacious when started as soon as possible to the onset of smell loss, when performed for 9 months, and when 12 essential oils are rotated to increase novelty—the introduction of additional essential oil scents has been termed Modified Olfactory Training. 52 Altundag et al 53 showed that this regimen also works for COVID-19-induced parosmia, significantly improving parosmia and quantitative olfaction as compared to controls ( P = .001 and P < .001, respectively).…”
Section: How Do We Currently Treat Parosmia?mentioning
confidence: 98%
“…Several studies have reported the effects of olfactory training in patients with COVID-19-associated olfactory dysfunction and that subjective and objective olfactory functions were significantly improved after olfactory training [ 23 , 24 ]. Denis et al performed olfactory training with a mean visual stimulation duration of 4 weeks in 548 patients with COVID-19-associated olfactory dysfunction.…”
Section: Reviewmentioning
confidence: 99%
“…Altundag et al performed modified olfactory training using 12 odorants during a 36-week period on 75 patients with COVID-19-associated parosmia, and reported a significant improvement in olfactory function in both treatment and non-treatment groups at the third, sixth, and ninth months. However, the degree of improvement was significantly higher in the treatment group than in the non-treatment group [ 24 ]. The authors also published an article about the effects of olfactory training in patients with persistent olfactory dysfunction for about 3 months.…”
Section: Reviewmentioning
confidence: 99%